2022
DOI: 10.3389/fmed.2022.878946
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Value of Spectral-Domain Optical Coherence Tomography for Polypoidal Choroidal Vasculopathy: A Systematic Review and Meta-Analysis

Abstract: PurposeTo evaluate the diagnostic value of spectral-domain optical coherence tomography (SD-OCT) for polypoidal choroidal vasculopathy (PCV).MethodsA search of electronic databases was conducted from 2010 to 2021 to review the relevant literature on SD-OCT to identify PCV and other lesions causing serious or serosanguinous retinal pigment epithelial detachment (PED), specifically neovascular age-related macular degeneration (nvAMD). The QUADAS-2 scale was used to evaluate the quality of the literature. We perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Permadi et al conducted a meta-analysis of 7 studies with 911 eyes and found a pooled sensitivity of 0.91, specificity of 0.88, and area under the receiver operating characteristics curve (AUC) of 0.9550. In another meta-analysis, Jiang and Qi51 included 12 studies with a total of 1348 eyes and found that the SD-OCT had a pooled sensitivity of 0.87 and a pooled specificity of 0.83 in diagnosing PCV, giving an AUC of 0.94.…”
Section: Updates On Diagnosis Of Pcvmentioning
confidence: 99%
“…Permadi et al conducted a meta-analysis of 7 studies with 911 eyes and found a pooled sensitivity of 0.91, specificity of 0.88, and area under the receiver operating characteristics curve (AUC) of 0.9550. In another meta-analysis, Jiang and Qi51 included 12 studies with a total of 1348 eyes and found that the SD-OCT had a pooled sensitivity of 0.87 and a pooled specificity of 0.83 in diagnosing PCV, giving an AUC of 0.94.…”
Section: Updates On Diagnosis Of Pcvmentioning
confidence: 99%